Konflik Relasi Komunikasi Masyarakat Jawa Transmigran dan Lampung di Kabupaten Lampung Timur - Wicaksono, Falah; Mukaromah, Lailatul; Khunna, Chutikarn; Hidayatullah, Ahmad Fauzan (Jurnal Ilmu Komunikasi, 2024)
Transmigration is a method used by the government to equalize the existence of the population in Indonesia. This transmigration is carried out from areas that are densely populated to areas that are sparsely populated. Likewise with the transmigration carried out by the government for residents on the island of Java to the island of Sumatra, especially Lampung. However, this has an impact on the social relations that occur, due to the different ethnic groups between immigrants and natives. The relationship between the two tribes that is not open makes frequent divisions between the two. The lack of adaptation of the Javanese to the new environment and the occurrence of social inequalities and cultural differences make them often contradictory and lead to conflicts. Therefore, the community has its own way of managing conflict, namely by limiting their association with different ethnic groups. The research method used is library research, namely by collecting information and data from libraries and the internet. The theory used is Behaviorism communication theory supported by American scientist John Broadus Watson.